Perubahan Pengaturan Masa Jabatan Hakim Konstitusi Dan Implikasinya Perspektif Pendekatan Sistem Jasser Auda - Alindra, Wahdiny Alindra 'Afwany (El-Dusturie, 2025)
Abstract: The DPR has again initiated changes to the term of office of constitutional judges through the Fourth Amendment to the Constitutional Court Law (UU MK). Through the revised draft that has been circulated in the public, the provisions on the term of office that were originally set until retirement age (age 70) as stated in Article 87 letter b of the MK Law, are to be changed to a term of office of 5-10 years with an evaluation mechanism by the proposing institution. This revision has reaped controversy in society, especially among legal experts and academics. Therefore, researchers will discuss the changes from the perspective of the Jasser Auda system approach. This system approach is important to use, because changes regarding the rules on the term of office must be considered comprehensively and based on clear parameters and benefits and can have a positive influence on the independence of the judiciary. This type of research is normative legal research with a statutory regulatory approach. The research method used is library research. The results of the study indicate that changes to the regulation on the term of office of constitutional judges do not meet the features of the Jasser Auda system approach and will later have implications for weakening the independence of judges and abuse of authority. This condition also has an impact on reducing the credibility of the Constitutional Court and injuring the principles of the rule of law and democracy. Keywords: Constitutional Judges; Term of Office; a System Approach of Jasser Auda Abstrak: DPR kembali menginisiasi perubahan masa jabatan hakim konstitusi melalui Perubahan Keempat Undang-Undang Mahkamah Konstitusi (UU MK). Melalui draf revisi yang telah tersebar di publik, ketentuan masa jabatan yang semula ditetapkan hingga usia pensiun (usia 70 tahun) sebagaimana tertuang dalam Pasal 87 huruf b UU MK, hendak dirubah dengan masa jabatan selama 5-10 tahun dengan mekanisme evaluasi oleh lembaga pengusul. Revisi ini telah menuai kontriversi di masyarakat khususnya para pakar hukum dan akademisi. Oleh karenanya, peneliti akan membahas perubahan tersebut menurut perspektif pendekatan sistem Jasser Auda. Pendelatan sistem ini penting untuk dipakai, sebab perubahan mengenai aturan masa jabatan haruslah dilakukan pertimbangan secara menyeluruh dan didasarkan pada parameter dan manfaat yang jelas serta dapat membawa pengaruh positif terhadap independensi kekuasaan kehakiman. Jenis penelitian ini adalah penelitian yuridis normatif dengan pendekatan peraturan perundang-undangan. Metode penelitian yang duganakan adalah studi kepustakaan (library research). Hasil penelitian menunjukkan bahwa perubahan pengaturan masa jabatan hakim konstitusi tidak memenuhi fitur-fitur pendekatan sistem Jasser Auda dan nantinya akan berimplikasi melemahkan independensi hakim dan penyalahgunaan wewenang. Kondisi tersebut juga membawa dampak bagi menurunnya kredibilitas Mahkamah Konstitusi dan tercederainya prinsip negara hukum dan demokrasi. Kata Kunci: Hakim Konstitusi; Masa Jabatan; Pendekatan Sistem Jasser Auda